Intentions to Return : Evidence from Romanian Migrants - Hinks, Tim; Davies, Simon (World Bank Group, Washington, DC, 2015)
Romania faces an acute population crisis with an aging workforce and an increased number of emigrants particularly from the young, highly educated/skilled population. This paper uses a new cross-sectional data set of Romanian emigrants to find which factors are related to plans to return home permanently. The analysis pays particular attention to differences in expected earnings and skills and training acquired as a migrant. The study finds that higher expected earnings in Romania and investment in Romanian firms are positively correlated with plans to return migrate. Policies that boost productivity and therefore wages as well as policies that improve the business climate could therefore encourage Romanian migrants to return to Romania, moderating the negative consequences of the declining and aging population, and increasing the skill stock of the Romanian labor force.